Disiplin Soruşturmalarında Hukuka Aykırı Deliller - (:unkn) unknown (My University, 2018)
Kamu görevlilerinin çalıştıkları kurumun düzenini bozan veya kurumun sunduğu hizmetin düzgünyürütülmesini engelleyen faaliyetleri disiplin hukukunun konusunu oluşturmaktadır. Disiplin hukukusöz konusu ihlalleri gerçekleştiren kamu görevlisinin daha dikkatli ve özenli davranmasını sağlayacak,mali haklarına ve mesleki statüsüne etki yapmaya yönelik disiplin cezalarını ve bu cezalara ilişkinbaşvurulabilecek yolları ve disiplin cezasının tesisi için gereken disiplin soruşturma sürecini konualmaktadır.Disiplin soruşturmasını yürüten soruşturmacı; soruşturma konusuyla sınırlı olmak üzere her nevievrakı incelemeye, ilgili kurumlardan ve kişilerden bilgi ve belge almaya, tanık dinlemeye, mahallindekeşif yapmaya, hakkında soruşturma yapılan memurun savunmasını almaya, soruşturma raporudüzenlemeye yetkilidir. Ancak, soruşturmacıya tanınan bu yetkilerin kullanımı sırasında veyasoruşturma raporunun tesisi sırasında yapılan değerlendirmelerde bazı hatalar, hukuka aykırılıklarmeydana geldiği de görülmektedir.Danıştay’ ın bir kısım kararlarında, disiplin hukukunun bağımsız olduğu, ceza soruşturmalarındandisiplin soruşturmalarını bağlamadığı ilkeleri zikredilerek, hukuka aykırı delillerin disiplinsoruşturmalarında kullanılmasına engel olmadığı yönünde hükümler tesis edilmiştir. Ancak, Danıştayyakın dönemlerde kararlarını değiştirmiş, Anayasamızın 38. maddesinde öngörülen hukuka aykırıelde edilen bulguların delil olarak kullanılmamasını yönündeki ilkenin disiplin soruşturmalarındauygulanması mümkün hale gelmiştir.

Disciplinary action is the activity of public officials whose activities disrupt the order of the institution or prevent the smooth execution of the service provided by the institution. Disciplinary law refers to the disciplinary penalties for affecting financial rights and professional status, the disciplinary proceedings process required for the establishment of disciplinary punishment, and the ways in which the public officer who performs the violations is more careful and attentive, Investigator conducting the disciplinary proceedings; to investigate all types of documents, to obtain information and documents from the related institutions and persons, to listen to witnesses, to make explorations on the spot, to take the defense of the investigated officer, to arrange an investigation report. However, it is also seen that some mistakes in the evaluations made during the use of these authorities known to the investigator or during the establishment of the investigation report have been contrary to the law. Some of the decisions of the Council of State have established provisions that disciplinary law is independent and that criminal investigations do not link disciplinary investigations with provisions that do not prevent the use of illegal evidence in disciplinary investigations. However, it is possible that the Council of State has recently changed it and applied it in the disciplinary proceedings of the original, which is not to be used as evidence for unlawful findings provided for in Article 38 of our Constitution.
Keywords: Hukuk